THE EFFECTS OF ENERGY DRINKS ON HEALTH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The literature review highlights the prevalence of energy drinks consumption, and describes their main ingredients (caffeine, taurine, guarana, ginseng, sweeteners). Numerous facts are given that testify to the negative impact on human health (including deaths) of the systematic use of large amounts of these beverages, both independently and in mixture with alcohol. It has been shown that the cardiovascular system, central nervous system and liver are most affected.